BOOKING SYSTEM BOARD ADS ON BUS SHELTERS - M. Fadjrin Gumilar; Rahayu Noveandini, S.Kom., MMSI (Jurnal Sistem Informasi, 2005)
Outdoor Advertising (outdoor advertising) can be viewed at around the city, either in the form of billboards or ads that are placed on the body of the bus. Unwittingly, the ad - that ad became one of the view that decorate the city. This research aims at describing the ordering system, especially that there are billboards on bus stops / bus shelters at PT IKRA sandalwood latitude, an advertising company that provides media production services Outdoor Advertising, located in the numbers Tebet, South Jakarta.